Integrated green cities: urban meets forest. A case study of the town of Trento. - Cantiani, Maria Giulia; Betta, Alessandro; De Meo, Isabella; Paletto, Alessandro; Tamanini, Sara; Maino, Federica (Springer, 2018)
A smart city is one which is liveable both from the natural and human-environment points of view and is also one where citizens are involved in the realization and management of an attractive urban environment of high quality. This requires an effective dialogue between citizens and institutions, which means, among other issues, that the planners' conception of urban, peri-urban and rural spaces is coupled with the inhabitants' perception of them and their sense of place. In light of the process of urbanization occurring in many towns of the Alpine Region, managers and planners need to know the new order of priorities in values expressed by the population with regard to forests. This paper illustrates a case study of the town of Trento, in the north-eastern Italian Alps, a typical medium-sized alpine town which, despite recent urbanization, is still in close proximity to forested areas. The research, carried out by means of a self-reporting questionnaire, was aimed at investigating the relationship between citizens and their forests. The data collected were analyzed statistically with special regard to sociodemographic characteristics. In particular, the Principal Component Analysis (PCA), applied to some questions investigating people's perception, made it possible to highlight visitors' preferences for forest features and the main functions attributed to the forests. The results show that urbanization and socioeconomic changes, with the introduction of an urban lifestyle, are producing a radical transformation in people's behavior and attitudes in relation to forests. A survey of this type may be a useful tool in helping future management and planning.
Keywords: Wald; Waldwirtschaft; Urbanisierung; Zersiedelung; Lebensstil; Erholung; Naherholung; Wertvorstellung; Wertewandel